Peningkatan Pemahaman dan Keaktifan Siswa Melalui Penerapan Model Pembelajaran Kooperatif Tipe TAI (Teams Assisted Individualization) di SMA Negeri 6 Surakarta - Kismanto Kismanto (Universitas Sebelas Maret, 2019)
This study aims to improve the understanding and active learning of students of opportunity material using cooperative learning models of the TAI (Teams Assisted Individualization). This research is a Classroom Action Research conducted in 2 cycles. Each cycle consists of 4 stages, namely planning, action, observation, and reflection. The research subjects were students of class XII IPA 2 of SMA Negeri 6 Surakarta in the academic year of 2018/2019. The results of the study concluded that the implementation of classroom action through the use of the TAI (Teams Assisted Individualization) type of cooperative learning model on the opportunity material can improve students' understanding and activeness in mathematics learning. This is based on test results and observations. From the test results in the first cycle, the percentage of students who completed was 62.96% and in the second cycle the percentage of students who completed experienced an increase of 33.33% to 96.29%. While the observations of the two observers, in the first cycle produced an average percentage of students' activeness reached 66.35% with a visual activity percentage of 83.2% and writing activity 61.22% and in the second cycle an increase in the average percentage of student activity by 20.92% to 87.27 % with the percentage of visual activity 85.88%, writing activities and activities 88.68%. These results it can be concluded that the application of the TAI (Teams Assisted Individualization) type of cooperative learning model can improve the understanding and activeness of learning in class XII Science 2 SMA Negeri 6 Surakarta odd semester 2018/2019